Educação para morte: pesquisa-ação com profissionais de enfermagem de uma unidade de terapia intensiva neonatal - Pilger, Carolina Heleonora (2023)
In the context of a Neonatal Intensive Care Unit (NICU), nursing professionals, whether nurses or nursing technicians, provide complex care with neonates, which are between life and death. Therefore, in addition to performing technical procedures, the professional needs to be prepared to deal with the death of patients who are under their care and perform the necessary care to the bereaved family. Therefore, this research aimed to propose, implement and evaluate an intervention for death education with nursing professionals of a NICU. Specific objectives: to understand the perceptions and feelings of nursing professionals facing the process of death and dying of neonates in a NICU; to collectively build and implement actions of education for death with nursing professionals of a NICU; to describe and evaluate the results of the actions developed with the nursing professionals of a NICU. This is a descriptive and exploratory study of qualitative approach of the type research-action, developed with 14 nursing professionals (nurses and nursing technicians) of a NICU, located in a municipality of the West Border of Rio Grande do Sul. Data collection occurred through individual semi-structured interview, seminar and application of a self-administered questionnaire at the end of the educational activity. The data were analyzed according to the discursive textual analysis. The research was approved by the Research Ethics Committee under opinion number 5,346,493. The participants were 14 nursing professionals, nursing technicians and nurses. After the interviews, five categories emerged: "Meanings attributed to death by nursing professionals of the Neonatal Intensive Care Unit"; "The performance of nursing professionals in the face of neonatal death"; "The ties and bonds established between professional, patient and family"; "Mourning and the struggle of parents in the face of the death of the Newborn" and "The need to talk about death throughout the training of the health professional". After the presentation of the results in the central seminars, it was decided as an educational action the construction of a booklet and video containing guidelines on mourning and reception in situations of neonatal loss. In general, the participants signaled the benefits that these materials brought, stating that they contributed to the understanding of aspects related to death, mourning and reception. Education for death, as a proposal developed in this research, intervened through educational actions in conjunction with nursing professionals of a NICU. It was a strategy that contributed to meet the desires and assist in reflection on neonatal death.